The scope and limits of accounting and judicial courts intervention in inefficient public procurement - Estache, Antonio; Foucart, Renaud (Elsevier, 2018)
Cost inefficiencies in public procurement tend to come from two sources: corruption (moral hazard) and incompetence (adverse selection). In most countries, audit authorities are responsible for monitoring costs but do not distinguish both sources of inefficiency in their audits. Judicial courts typically rely on these cost audits, but only sanction corruption. In a model of public procurement by politicians, we study how the respective quality of the two courts affects corruption as well as cost efficiency. We find that while better courts have the direct effect of decreasing corruption, they may have a negative indirect effect on the abilities of the pool of politicians, so that the net effect on cost efficiency is ambiguous.